Sosialisasi Digital Marketing dan e-Commerce pada Siswa SMP-SMA Adi Sucipto di Desa Teluk Kapuas - Pangestu, Gavin Satria; Atadius, Deodatus; Dharma, Dharma; Akbar, Tegar Surya; Adiloka, Mohammad Fonsitama; Sulistiowati, Sulistiowati (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Teluk Kapuas Village faces economic and environmental challenges, with the MSME sector still not developing and the low quality of the products produced. One of the main problems is students' lack of knowledge about digital marketing and e-commerce, which can support the development of MSMEs. The socialization program designed aims to provide education to students regarding digital marketing and e-commerce. It is hoped that this program will improve the skills of the younger generation in digital technology so that they can contribute to increasing the quality and quantity of MSMEs in villages. Through this program, students gain a better understanding of digital marketing strategies, the use of e-commerce platforms, as well as the importance of an online presence in business. Program results show increased student understanding of the topic, which is expected to support local economic growth. is expected to support local economic growth.